Avaliação cardiorrespiratória e de sedação da associação de dexmedetomidina-butorfanol-midazolam ou detomidina-butorfanol-midazolam em catetos (Pecari tajacu) - Renata Andrade Silva (2017)
The management of wild animals in captivity requires safe and effective containment methods that ensure adequate immobilization to perform management practices, such as identification, separation by age group, collection of biological material, morphometric measurements, physiological measurements and treatment of diseases. At these times, the animals may develop some clinical manifestations called stress syndrome, malignant hyperthermia or capture myopathy, which may result in death. In some situations, chemical containment is fundamental in the performance of this management, especially of potentially aggressive individuals, suppressing their irritability and reactions caused by animal stress. The aim of the present study was to compare the cardiorespiratory, hemogasometric and sedative effects of midazolam-butorphanol plus detomidine or dexmedetomidine combination in catheters. Twenty adult catheters weighing on average 18.5 ± 5.4 kg were randomly distributed into two groups (n = 10): dexmedetomidine (36 g / kg), burtorfanol (0.31 mg / kg) and midazolam (0.41 mg / kg), IM or detomidine (157 g / kg), butorphanol (0.31 mg / kg) and midazolam (0.42 mg / kg), IM. The variables (HR, RR, MAP, SpO2, ETCO2 and RT) were evaluated after application of the drugs (containment cage). Five moments were evaluated, being M0 (after instrumentation), M1, M2, M3 and M4 (every 10 minutes). Hemogasometry and lactate dosage were performed in M0 and M4 (arterial blood). Sedation was assessed by visual analogue scale, muscle relaxation, posture and auditory response. ANOVA was performed followed by paired t test (parametric) and Mann Whitney Rank Sum Test (non-parametric) with p <0.05. No statistical difference was observed for the latency period, being 5.9 ± 1.3min (dexmedetomidine) and 7.1 ± 2.6min (detomidine). A significant increase was observed between groups for the variables RR, MAP and SpO2 with higher values for detomidine and ETCO2 with higher values for dexmedetomidine. In the evaluation between moments the dexmedetomidine group reduced significantly 20% in HR in M4 (103 ± 14/83 ± 9), lactate reduced by 65% (11.1 ± 5.0 / 3.9 ± 2.5) and HCO3 Increased by 50% (20.6 ± 4.8 / 30.1 ± 2.5). The detomidine group presented the same changes as the dexmedetomidine group between moments, with a decrease of 14% for HR (97 ± 18/83 ± 13, 57) and 65% for lactate (12.14 ± 6/4, 23 ± 2.17), in addition to an increase of 48% for HCO3 (19.5 ± 7.5 / 28.9 ± 3.5). SpO2 remained below 90% throughout the experiment in both groups. SpO2 remained below 90% throughout the experiment in both groups. The animals of both groups presented deep sedation and maximum muscle relaxation. It was concluded that the associations between dexmedetomidine-butorphanol-midazolam and detomidine-butorphanol-midazolam in the doses used provided adequate sedation, but with SpO2 alterations. Thus, both are indicated for chemical containment of adult hounds.